2019
DOI: 10.1016/j.wear.2019.202962
|View full text |Cite
|
Sign up to set email alerts
|

FE8 type laboratory testing of white etching crack (WEC) bearing failure mode in 100Cr6

Abstract: WEC is an aggressive and unpredictable failure mode affecting bearings in particular in the wind energy sector. This paper focuses on the most common used method for WEC laboratory accelerated testing, the FE8 type test rigs using martensitic through hardened 100Cr6 cylindrical roller thrust bearings, analyzing the load conditions, test results and damage quantification. The surface and subsurface stress conditions as well as the surface frictional loading were analyzed using a half-space model. Simulations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…The test conditions are characterised by an axial load of 60 kN, a shaft speed of 300 rpm and a bearing temperature of 100 °C. These conditions have been previously used in further FE8 related WEC studies such as (Danielsen et al, 2019). As shown in the work of DANIELSEN (Danielsen et al, 2019) these conditions usually lead to failures between 100 h and 300 h.…”
Section: Development Of a Roller Bearing Damagementioning
confidence: 99%
“…The test conditions are characterised by an axial load of 60 kN, a shaft speed of 300 rpm and a bearing temperature of 100 °C. These conditions have been previously used in further FE8 related WEC studies such as (Danielsen et al, 2019). As shown in the work of DANIELSEN (Danielsen et al, 2019) these conditions usually lead to failures between 100 h and 300 h.…”
Section: Development Of a Roller Bearing Damagementioning
confidence: 99%
“…Two lubricants are used in the tests on the roller bearing test rig. The first lubricant is a fully-formulated mineral oil from a group I base oil with a viscosity class ISO VG 100 and referred to as "mineral oil" in the following, which has already been used in previously published work [28][29][30][31][32]. Analysis results of the elemental analysis are shown in Table 1.…”
Section: Lubricantsmentioning
confidence: 99%
“…Both the bearing washers and the rollers are made of martensitic through-hardened 100Cr6 steel (AISI 52100). In alignment with previously conducted investigations, a polyamide cage (PA66) with fifteen rollers was used [28][29][30][31][32]. Figure 1(b) shows exemplarily the FE8 test rig for cylindrical roller thrust bearings of the type 81212, comprehensive details of which can be seen in Refs.…”
Section: Test Bearingsmentioning
confidence: 99%
See 1 more Smart Citation
“…These hypotheses are mainly based on tests of 81212 bearings on FE-8 rigs with a ''WEC-critical'' oil. [15][16][17][18][19] Based on this, it is suggested that WECs develop due to high frictional energy accumulation, 20,21 promoted by specific additives, [22][23][24][25][26] which lead to hydrogen ingress and subsequent weakening of the material. 4,19,23,[27][28][29][30] Lubricant additives, specifically extreme pressure and anti-wear (EP/AW) additives, are used to prevent from surface deterioration in mixed lubrication, notably to compensate lower and lower base oil viscosities.…”
Section: Introductionmentioning
confidence: 99%